Pelatihan Proses Produksi dan Branding Packaging (Pengemasan) Pada Kelompok Penderes Gula Merah Desa Gintangan Kab. Banyuwangi - Oktavima Wisdaningrum; Rahayuningsih Rahayuningsih; Khoirul Bariyyah (IAI Darussalam, 2018)
The main objective of this training program is to train community groups in the production process and branding packaging (packaging) of brown sugar for the products produced by the group of beneficiaries. The training location is in Gumuk Agung Village, Gintangan Village, Banyuwangi Regency. The method used is the method of lecture, discussion and practice. This socialization (training) was given to Sinar and Tunas Jaya Gintangan Banyuwangi groups. The results achieved in this community partnership program are partners who understand about the production process of good brown sugar with hygienic conditions of materials and tools so as to produce healthy and quality products, besides the diversification of products in the form of ant sugar can be an additional producer for Gumuk Agung, and with the packaging of attractive products for brown sugar and ant sugar the products sold are bought to consumers becoming more attractive and value-added.